The integration of mobile learning among esl teachers to enhance vocabulary learning - Hafizah Muhamad Kassim; Nur-Ehsan Mohd Said (Indonesian Institute for Counseling, Education and Theraphy, 2020)
This study intended to describe seven ESL teachers’ integration and their attitudes toward mobile learning (m-learning) as a tool to facilitate students in vocabulary lessons. Mobile learning is a new way to access learning content using handheld devices where mobile technology is integrated into routine teaching activities. The concept is grounded on a theoretical foundation where the mobile application is used as a tool to enhance learning. A qualitative research approach was employed for data collection and analysis in the study. Seven respondents of ESL teachers at secondary schools participated in a series of semi-structured interviews. The interview protocol was adapted from the Unified Theory of Acceptance and Use of Technology (UTAUT) to understand the ESL teachers’ practice regarding the integration of mobile learning. Findings from the study indicated that the ESL teachers integrated mobile learning in their teaching due to its functionality in enhancing English language learners’ vocabulary learning. The study indicated that the teachers considered mobile learning as necessary and a convenient type of learning while displaying positive attitudes towards the integration of mobile learning. Regardless of their length in service or volition, mobile learning is seen as one of the many useful tools that facilitate vocabulary lessons.